(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article presents the developed classification of micromechanical elements, as well as the calculations and fabrication of micromechanical elements of the beam type, using the theory of elasticity and the Finite Element Method (FEM). The principle of etching a conventional angle and partial etching of freely vibrating components is considered. The technical model of the clamped beam, physical and mathematical modeling, as well as simulation and verification of correctness are described. The relationship between the design and entry into the database of the automated design system "MICROSYS 25" of microsystem engineering products is presented.